Nanometre imaging of Fe3GeTe2 ferromagnetic domain walls. (23rd February 2021) - Hopkinson, David G; Seki, Takehito; Clark, Nicholas; Chen, Runze; Zou, Yichao; Kimura, Ayumi; Gorbachev, Roman V; Thomson, Thomas; Shibata, Naoya; Haigh, Sarah J
Abstract: Fe3 GeTe2 is a layered crystal which has recently been shown to maintain its itinerant ferromagnetic properties even when atomically thin. Here, differential phase contrast scanning transmission electron microscopy is used to investigate the domain structure in a Fe3 GeTe2 cross-sectional lamella at temperatures ranging from 95 to 250 K and at nanometre spatial resolution. Below the experimentally determined Curie temperature ( T C ) of 191 K, stripe domains magnetised along ⟨0001⟩, bounded with 180 ◦ Bloch type domain walls, are observed, transitioning to mixed Bloch−Néel type where the cross-sectional thickness is reduced below 50 nm. When warming towards T C, these domains undergo slight restructuring towards uniform size, before abruptly fading at T C . Localised loss of ferromagnetic order is seen over time, hypothesised to be a frustration of ferromagnetic order from ambient oxidation and basal cracking, which could enable selective modification of the magnetic properties for device applications.